Effect of Endometrium Thickness on Clinical Outcomes in Luteal Phase Short-Acting GnRH-a Long Protocol and GnRH-Ant Protocol - Zhang, Jie; Sun, Yi-Fei; Xu, Yue-Ming; Shi, Bao-jun; Han, Yan; Luo, Zhuo-Ye; Zhao, Zhi-Ming; Hao, Gui-Min; Gao, Bu-Lang (Frontiers in Endocrinology, 2021)
Objective To investigate the factors that influence luteal phase short-acting gonadotropin-releasing hormone agonist (GnRH-a) long protocol and GnRH-antagonist (GnRH-ant) protocol on pregnancy outcome and quantify the influence. About the statistical analysis, it is not correct for the number of gravidities. Methods Infertile patients (n = 4,631) with fresh in-vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) and embryo transfer were divided into GnRH-a long protocol (n =3,104) and GnRH-ant (n =1,527) protocol groups and subgroups G1 (EMT ≤7mm), G2 (7 mm <EMT ≤10 mm), and G3 (EMT >10 mm) according to EMT on the trigger day. The data were analyzed. Results The GnRH-ant and the GnRH-a long protocols had comparable clinical outcomes in the clinical pregnancy, live birth, and miscarriage rate after propensity score matching. In the medium endometrial thickness of 7–10 mm, the clinical pregnancy rate (61.81 vs 55.58%, P < 0.05) and miscarriage rate (19.43 vs 12.83%, P < 0.05) of the GnRH-ant regime were significantly higher than those of the GnRH-a regime. The EMT threshold for clinical pregnancy rate in the GnRH-ant group was 12 mm, with the maximal clinical pregnancy rate of less than 75% and the maximal live birth rate of 70%. In the GnRH-a long protocol, the optimal range of EMT was >10 mm for the clinical pregnancy rate and >9.5 mm for the live birth rate for favorable clinical outcomes, and the clinical pregnancy and live birth rates increased linearly with increase of EMT. In the GnRH-ant protocol, the EMT thresholds were 9–6 mm for the clinical pregnancy rate and 9.5–15.5 mm for the live birth rate. Conclusions The GnRH-ant protocol has better clinical pregnancy outcomes when the endometrial thickness is in the medium thickness range of 7–10 mm. The optimal threshold interval for better clinical pregnancy outcomes of the GnRH-ant protocol is significantly narrower than that of the GnRH-a protocol. When the endometrial thickness exceeds 12 mm, the clinical pregnancy rate and live birth rate of the GnRH-ant protocol show a significant downward trend, probably indicating some negative effects of GnRH-ant on the endometrial receptivity to cause a decrease of the clinical pregnancy rate and live birth rate if the endometrial thickness exceeds 12 mm.